THU0057 Lipid profiling of plasma in rheumatoid arthritis patients by liquid chromatography–tandem mass spectrometry. (15th June 2017) - Murakami, K; Murakami, I; Ioan-Facsinay, A; Giera, M; Hashimoto, M; Yoshida, A; Usui, T; Kuramoto, N; Nakashima, R; Imura, Y; Yoshifuji, H; Ohmura, K; et al.
Abstract : Background: Previously it has been described that lipid and lipid mediators are present in synovial fluid from patients with rheumatoid arthritis (RA). It is, however, currently unknown to what extent these lipid mediators are involved in disease pathophysiology. Objectives: The aim of this study is to clarify which lipid mediators in plasma correlate with disease activity of RA. Methods: We obtained blood from RA patients registered in the KURAMA (Kyoto University Rheumatoid Arthritis Management Alliance) cohort. None of the patients was treated with glucocorticoids or NSAIDs, both of which could affect lipid metabolism. Targeted lipidomics, using a LC–MS/MS (liquid chromatography–tandem mass spectrometry) platform was used for the identification of lipids present in the patients' plasma. SDAI (simplified disease activity index) was examined in this cohort and lipidomics profiling and disease status were combined. Data were statistically analyzed by Spearman's rank correlation coefficient test or multivariate regression analysis. Results: Twenty-six RA patients were enrolled; female ratio: 84%, mean age: 63.0 years old, mean disease duration: 18.7 years and mean SDAI 5.26. In this group, patients age was significantly correlated with SDAI (p value =0.005, Spearman's rho =0.552). By LC-MS/MS analyses, 23 lipid components were identified and quantified. Multivariative regression analysis (Standard Least Squares) revealed that 19, 20-diHDPA (Dihydroxydocosapentaenoic acid) and 14, 15-diHETE (Dihydroxyeicosatetraenoic acid) significantly explained SDAI score independently of sex and age. Among the composite measure for SDAI, the best correlated component with TJC (tender joint count) was LA (Linoleic acid, p=0.002, rho = -0.611), that with patient VAS (visual analogue scale) was 19, 20-diHDPA (p=0.032, rho =0.440), and that with CRP was DHA (Docosahexaenoic acid, p=0.021, rho = -0.452). Additionally, principal component analysis was carried out. In the first primary component (PC1), absolute eigenvecotor values of AdA (Adrenic acid), ALA (Alpha-linolenic acid), DHA, DPA (Docosapentaenoic acid) and LA are more than 0.25, among which DHA was strongly correlated with PC1 (p<0.0001, rho =0.902). PC1 positively and significantly explained TJC count independent of sex and age. Conclusions: Since 19, 20-diHDPA (metabolized from DHA) and 14, 15-diHETE (from EPA, eicosapentaenoic acid) are both generated by cytochrome P450-catalyzed epoxidation followed by conversion to the vicinal diols by epoxide hydrolase, such kind of enzymes might be key molecules connecting lipid metabolism and RA. Although a replication study is inevitable, a certain kinds of lipid and lipid mediator profiles may be associated with disease activity, especially analgesic descriptors such as tender joint count. References: Giera M, et al. Lipid and lipid mediator profiling of human synovial fluid in rheumatoid arthritis patients by means of LC-MS/MS. Biochim Biophys Acta. 2012, 1821(11):1415–24. Acknowledgements: None. Disclosure of Interest: None declared